2016
DOI: 10.1021/acs.jpcc.6b02980
|View full text |Cite
|
Sign up to set email alerts
|

Unconventional Electronic Properties of Mg2Si Thermoelectrics Revealed by Fast-Neutron-Irradiation Doping

Abstract: In this work, we systematically investigated the electrical resistivity, Hall, and magnetoresistance effects of Aldoped Mg 2 Si thermoelectrics, irradiated with a fluence of fast neutrons and consequently isochronally annealed at moderate high temperatures up to 500 °C. We found that the fastneutron bombardment itself only slightly modified the electronic properties. Meanwhile, a series of the postirradiation high-temperature anneals affected the properties dramatically. Thus, after annealing at temperatures o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2017
2017
2020
2020

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 92 publications
0
2
0
Order By: Relevance
“…The application of pressure or stress to members of another thermoelectric family based on the Group IV elements, namely, Mg 2 X (where X = Si, Ge, Sn), which crystallize in a cubic anti-CaF 2 -type structure (Fig. 1), 164,165 demonstrated that this method is capable of enhancing their thermoelectric properties. An experimental room-temperature study showed that both the electrical resistivity and Seebeck coefficient of n-type Mg 2 Si:Al decrease dramatically with pressure [ Fig.…”
Section: Journal Of Applied Physicsmentioning
confidence: 99%
“…The application of pressure or stress to members of another thermoelectric family based on the Group IV elements, namely, Mg 2 X (where X = Si, Ge, Sn), which crystallize in a cubic anti-CaF 2 -type structure (Fig. 1), 164,165 demonstrated that this method is capable of enhancing their thermoelectric properties. An experimental room-temperature study showed that both the electrical resistivity and Seebeck coefficient of n-type Mg 2 Si:Al decrease dramatically with pressure [ Fig.…”
Section: Journal Of Applied Physicsmentioning
confidence: 99%
“…This approach has been used in both experimental and theoretical explorations for various thermoelectrics, e.g. Bi 2 Te 3 -Sb 2 Te 3 alloys , BiTeI [31], Bi [32][33][34], PbTe [34][35][36][37], Mg 2 Si alloys [38][39][40][41][42][43][44], SnSe [45], MgAgSb [46], ZnGeSb 2 [47] and some others. The results gathered in these works testified that this method is indeed very promising.…”
Section: Introductionmentioning
confidence: 99%